2019
DOI: 10.3153/fh19002
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antioxidant Activity of Mycelial Extracts of Different Pleurotus Species

Abstract: Mushrooms could be used as a potential means of producing natural antioxidants and antimicrobials. To obtain fungal biomass in submerged culture is an easy and rapid method. For this reason, biomasses of Pleurotus species which grown on liquid media were used to prepare hot water extracts and their antioxidant and antibacterial properties were determined. The highest total phenolic content was determined in P. ostreatus extract (9.14 mg.g-1 dry weight of extract) whereas Pleurotus sajor-caju gave highest readi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
5
7
0
Order By: Relevance
“…Fungi themselves and extracts have antimicrobial effect. It has been reported to have higher activity, especially against Gram-positive bacteria (Reis, 2017;Ozdal et al 2019). In our study, Pleurotus and Lentiudes extracts were found their antibacterial effect on the bacterial species (P. aeuriginosa, S. aureus, E. coli, B. cereus, B. thuringiensis C. diphteria, K. oxycota, S. marcescens and E. faecalis).…”
Section: Quorum Sensing Inhibition Testssupporting
confidence: 56%
See 2 more Smart Citations
“…Fungi themselves and extracts have antimicrobial effect. It has been reported to have higher activity, especially against Gram-positive bacteria (Reis, 2017;Ozdal et al 2019). In our study, Pleurotus and Lentiudes extracts were found their antibacterial effect on the bacterial species (P. aeuriginosa, S. aureus, E. coli, B. cereus, B. thuringiensis C. diphteria, K. oxycota, S. marcescens and E. faecalis).…”
Section: Quorum Sensing Inhibition Testssupporting
confidence: 56%
“…ostreatus and P. sajor-caju were grown at 25 ℃ for 7 days on Potato Dextrose Agar (PDA). Submerged fermentation was achieved in 250 mL Erlenmeyer flasks, containing 100 mL of liquid medium (Ozdal et al 2019). Each flask was inoculated with one 10 mm agar plugs.…”
Section: Culture and Fermentation Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the bacteria tested were resistant in this study, the inhibition of P. aeruginosa using biomass extracted from P. eryngii, P. sajor-caju, P citrinopileatus, P. ostreatus and P. florida in hot water has been mentioned in the literature, and presented an IH which was equivalent to 8.8, 9.0, 8.1, 9.4 and 9.7 mm, respectively (Özdal, Gülmez, Gür-Özdal, & Algur, 2019). Similarly, Fasoranti, Ogidi, and Oyetayo (2018) verified the sensitivity of P. aeruginosa (IH= 14 and 15 mm), S. aureus (IH= 13.7 and 15.7 mm) and E. coli (IH= 15.7 and 14 mm), in relation to the mushrooms P. pulmonarius and P. ostreatus.…”
Section: Resultsmentioning
confidence: 69%
“…Similarly, Liu and Wang [ 63 ] used a mixture of glucose and corn extract as a source of glucose and wheat bran and yeast extract as a source of nitrogen in a 30 L bioreactor with an agitated rate of 160 rpm, and a biomass value of 11.30 g/L was then recorded. In experiments with five species of Pleurotus grown for 15 days in a medium containing 20 g/L glucose, 2 g/L peptone and 3 g/L yeast extract, P. eryngii produced 6.1 g/L of biomass, whereas P. ostreatus produced 11.2 g/L [ 64 ]. Kim et al [ 27 ] cultured P. ostreatus in conditions similar to the present study and observed smaller values of produced biomass on the 5th, 10th and 15th culture days—1.07, 4.6 and 7.35 g/L, respectively.…”
Section: Resultsmentioning
confidence: 99%